Merekam Sejarah Industri Kopi Nur di Sungai Penuh (1984-2019) - Feldisa Sekar Wulandari; Midawati Midawati (Analisis Sejarah, 2023)
This article aims to address the issues related to the development of Kopi Nur industry in Sungai Penuh over the period from 1984 to 2019. The industry had two leadership periods: Nurcaya's leadership from 1984 to 2015, and Zefri Efdison's leadership from 2015 to 2019. The research employs a historical method, encompassing heuristic data collection, source criticism, interpretation, and historiography. During the heuristic phase, primary sources such as books, government-related data, relevant scholarly articles, certificates, and company records were collected. Interviews with informants were also conducted. Under Nurcaya's leadership from 1984 to 2015, Kopi Nur initially used water wheels for production but shifted to machinery due to increased demand. During Zefri Efdison's leadership, rapid coffee industry growth occurred due to effective sales management and workforce handling. To boost consumer interest, Zefri Efdison engaged in exhibitions and training programs. The study's findings conclude that Kopi Nur originated from Bukit Apit coffee in Bukittinggi and evolved into a family business under Nurcaya. Over 35 years since the introduction of the Kopi Nur brand, significant development has occurred, yielding positive impacts on the sustainability of Kopi Nur business.